Critical Examination of the Circumstantial Evidence Threshold in Competition Law: Obstacle or Legal Certainty? - Fatma Astiti Harun (SEAN Institute, 2026)
The use of circumstantial evidence is indispensable in competition law enforcement, as direct evidence of anticompetitive agreements is rarely available. However, the appropriate threshold for such evidence remains deeply contested, raising a fundamental tension between effective deterrence and legal certainty. This normative legal research, employing comparative and teleological analysis of Indonesian, European Union, and United States jurisprudence, critically examines whether the circumstantial evidence threshold operates as an obstacle to enforcement or as a safeguard for predictability. The findings reveal that an excessively high threshold requiring exclusion of all plausible alternative explanations creates a safe harbor for sophisticated cartels, particularly disadvantaging agencies with limited investigative powers such as Indonesia's KPPU. Conversely, an overly low and unstructured threshold risks false positives, condemning legitimate parallel conduct in oligopolistic markets and chilling pro-competitive behavior. Neither extreme is defensible. The study concludes that the optimal framework lies in a balanced, structured approach: competition authorities must present a consistent and objective body of circumstantial facts establishing a plausible inference of collusion, after which defendants may articulate non-collusive alternatives, with the ultimate burden remaining on the authority. This balanced threshold harmonizes enforcement efficacy with legal certainty, ensuring that competition law protects consumer welfare without sacrificing due process.